Gut Microbiome in Critical Illness (Review) - E. A. Chernevskaya (Obŝaâ Reanimatologiâ, 2018)
Radical changes in the composition, diversity and metabolic activity of gut microbiome in critically ill patients most probably affect adversely the outcome of treatment. Microbiota dysfunction may be a predictor and presumably the main cause of infectious complications and sepsis. Clinicists use objective scales for evaluation of patient condition severity including specific parameters of disorders of organs and systems; however, microbiota function is not considered specific and, hence, not evaluated. Technical capabilities of the recent decade have allowed characterizing the intestinal microbiota and that helped understanding the ongoing processes. The authors have analyzed data about the role of intestinal microbiota as a metabolic 'reactor' during critical states, possible complications related to misbalance of 'harmful' and 'beneficial' bacteria, and examined potential of a targeted therapy aimed directly at correction of intestinal microbiota. Search for papers was carried out using Scopus and Web of Science databases 2001 to 2018 years: (Gut Microbiota) AND (Critically ill OR Intensive care unit), key words taken for the search were: intestinal microbiota, metabolism, sepsis, antibiotics, critically ill patients, multiple organ failure. A number of questions in understanding of the interaction between gut microbiome and host remain open. It is necessary to take into account interference of microbial metabolism while assessing metabolome of patients with sepsis. Among low-molecular compounds found in blood of sepsis patients, special attention should be paid to molecules that can be classified as ‘common metabolites’ of humans and bacteria, for example, degradation products of aromatic compounds, which many-fold rise in blood of septic patients. It is necessary to take into consideration and experimentally model changes in the human internal environment, which occur during radical transformation of microbiome in critically ill patients. Such approach brings in new prospects for objective monitoring of diseases by evaluating metabolic profile at a particular moment of time based on integral indices reflecting the status of microbiome/metabolome system, which will supply new targets for therapeutic intervention in future.